2021
DOI: 10.3390/ani11020409
|View full text |Cite
|
Sign up to set email alerts
|

Selection Criteria for Improving Fertility in Spanish Goat Breeds: Estimation of Genetic Parameters and Designing Selection Indices for Optimal Genetic Responses

Abstract: The aim of this study was to estimate genetic parameters for several female fertility criteria and to choose the most suitable selection index in Spanish Florida and Payoya goat breeds. In this study, we analyzed as fertility traits, the age at first kidding (AgFiKid), and the interval between the first and second kiddings (Int12Kid), between the second, third, and remaining kiddings (Int3toKid), and between all kiddings (IntAllKid) in 51,123 and 22,049 Florida and Payoya females, respectively. Genetic paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…For example, Jembere et al (2017) in their meta-analysis of several studies on dairy goat breeds reported h 2 values of 0.17 ± 0.012 for the age at first kidding, 0.002 ± 0.018 for the first kidding interval, and 0.09 ± 0.01 for the interval between all kidding. Similarly, in our previous study on estimating genetic parameters for the classical fertility traits in the Florida and Payoya breeds, we obtained very low h 2 estimates, varying from 0.01 for the interval between second, third, and remaining kiddings in Florida to 0.11 for the age at first kidding in Payoya (Ziadi et al 2021a). Besides, the higher expected genetic responses calculated using selection indices occurred when the interval between all kiddings was combined with the age at first kidding.…”
Section: Genetic Parameters Of Reproductive Efficiencysupporting
confidence: 51%
See 3 more Smart Citations
“…For example, Jembere et al (2017) in their meta-analysis of several studies on dairy goat breeds reported h 2 values of 0.17 ± 0.012 for the age at first kidding, 0.002 ± 0.018 for the first kidding interval, and 0.09 ± 0.01 for the interval between all kidding. Similarly, in our previous study on estimating genetic parameters for the classical fertility traits in the Florida and Payoya breeds, we obtained very low h 2 estimates, varying from 0.01 for the interval between second, third, and remaining kiddings in Florida to 0.11 for the age at first kidding in Payoya (Ziadi et al 2021a). Besides, the higher expected genetic responses calculated using selection indices occurred when the interval between all kiddings was combined with the age at first kidding.…”
Section: Genetic Parameters Of Reproductive Efficiencysupporting
confidence: 51%
“…Genetic parameters of fertility in Spanish dairy goats were estimated only in one study for the age at first kidding and the different intervals between kidding in the Florida and Payoya populations (Ziadi et al 2021a) and, as expected for this kind of traits, the magnitude of estimates was relatively low. However, this study used a repeatability model and did not deal with fertility over a time trajectory.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The fertility of the individuals was assessed using the reproductive efficiency (Re) parameter (Ziadi et al., 2021), estimated as the deviation in percentage of the number of calvings that an animal has at each age, from the number of calvings that it could have had in optimal conditions. In the Retinta breed, the optimum age at first calving was considered 2 years and one year for the optimal calving interval, as in the majority beef cattle breed.…”
Section: Methodsmentioning
confidence: 99%